Gest\~ao do conhecimento estratégico em instituiç\~oes de ensino superior - Youssef Ahmad Youssef; Baltazar de' Andrade (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2010)
– The main goal of this paper intends to present as result, a new model of strategic knowledge management for Higher Education Institutions starting from the premise of the interaction absence between the strategic thought in institutions of higher education and the knowledge management of their collaborators. This model can help in the resolution of one another problem witch is based on the absence of a formal methodology for strategic plan implementation in Higher Education Institutions thru the knowledge management. For the deployment of this proposal we intend to use descriptive research of qualitative matrix using the natural environment of an higher education institution and having as stages the collection of: basic data, bibliographical revision on the evolution of the strategic thought and its interaction with the knowledge management thru out the organizations, theoretical analysis and finally the elaboration and the description of the new interaction model between the strategic thought and the knowledge management in the Higher Education Institutions.
Keywords: 330; Knowledge Management; Strategic planning; Strategic thinking IES (Institution of Higher Education)